CD123-Directed Bispecific Antibodies for Targeting MDS Clones and Immunosuppressive Myeloid-Derived Suppressor Cells (MDSC) in High-Risk Adult MDS Patients - Uckun, Fatih M.; Watts, Justin (Frontiers in Aging, 2021)
There is an urgent need to identify effective strategies to prevent leukemic transformation and induce sustained deep remissions in high-risk myelodysplastic syndrome (MDS) patients. This article discusses the clinical impact potential of bispecific antibodies (BiAB) capable of redirecting host T-cell cytotoxicity in an MHC-independent manner to malignant clones as well as immunosuppressive myeloid-derived suppressor cells (MDSC) as a new class of anti-MDS drug candidates. T-cell engaging BiAB targeting the CD123 antigen may help delay disease progression in high-risk MDS and potentially reduce the risk of transformation to secondary AML.